Exploring Madrasah Ibtidaiyah Students’ English Vocabulary Learning Through Duolingo Application - Silviatus Shoimah; Zainuddin Zainuddin; Nina Agus Hariati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
Vocabulary mastery is a fundamental challenge for young learners, particularly in Islamic elementary school environments where traditional textbook-based methods often lead to passive engagement and limited memory retention. This study aims to explore the implementation of the Duolingo application in supporting English vocabulary learning and to identify the specific learning activities facilitated by the platform. Using a qualitative descriptive research design, the study involved 26 fifth-grade students at MI Khilafiyah Syafi'iyah Zainul Hasan Genggong. Data were collected through classroom observations and semi-structured interviews with the teacher and students. The results reveal that Duolingo was successfully implemented through projector-based guided instruction, fostering a dynamic and enthusiastic classroom atmosphere. Six main types of vocabulary activities were identified: matching images, listening exercises, repetition, meaning recognition, vocabulary matching, and completing sentences. These activities utilized multimedia and gamification elements to enhance students' cognitive engagement and confidence. The study concludes that Duolingo serves as an effective pedagogical tool to overcome attention span limitations and strengthen long-term memory through sensory-based repetition. For practitioners, integrating such digital media collectively is recommended to facilitate social interaction and meaningful learning experiences. Keywords: Digital Learning, Duolingo, English Vocabulary, Madrasah Ibtidaiyah, Young Learners